Global Forum: An International Perspective on Outpatient Surgical Procedures for Adult Hip and Knee Reconstruction. (6th July 2016) - Argenson, Jean-Noël A.; Husted, Henrik; Lombardi, Adolph; Booth, Robert E.; Thienpont, Emmanuel
Abstract : Abstract: Outpatient surgical procedures for adult hip and knee reconstruction are gaining interest on a worldwide basis and have been progressively increasing over the last few years. Preoperative screening needs to concentrate on both the patient's comorbidities and home environment to provide a proper alignment of expectations of the surgeon, the patient, and the patient's family. Preoperative multidisciplinary patient information covering all aspects of the upcoming treatment course is a mandatory step, focusing on pain management and early mobilization. Perioperative pain management includes both multimodal and preventive analgesia. Preemptive medications, minimization of narcotics, and combination of general and regional anesthesia are the techniques required in joint arthroplasty performed as an outpatient surgical procedure. A multimodal blood loss management program should be used with preoperative identification of anemia and attention directed toward minimizing blood loss, considering the use of tranexamic acid during the surgical procedure. Postoperative care extends from the initial recovery from anesthesia to the physical therapist's evaluation of the patient's ambulatory status. After the patient has met the criteria for discharge and has been discharged on the same day of the surgical procedure, a nurse should call the patient later at home to check on wound status, pain control, and muscle weakness, which will be further addressed by physiotherapy and education. Implementing outpatient arthroplasty requires monitoring safety, patient satisfaction, and economic impact.